Uncle Tom's cabin - Stowe, Harriet Beecher, 1811-1896 (Oxford University Press, 1998)
Labeled racist and condescending by some contemporary critics, this novel remains a shocking, controversial, and powerful work that exposes the attitudes of white 19th century society toward the institution of slavery.
Keywords: Uncle Tom -- (Fictitious character) -- Fiction.; Uncle Tom -- (Fictitious character); Master and servant -- Fiction.; African Americans -- Fiction.; Fugitive slaves -- Fiction.; Plantation life -- Fiction.; Southern States -- Fiction.; Slavery -- Fiction.; Enslaved persons -- Fiction.; Noirs américains -- Romans, nouvelles, etc.; Esclaves fugitifs -- Romans, nouvelles, etc.; Vie dans les plantations -- Romans, nouvelles, etc.; États-Unis (Sud) -- Romans, nouvelles, etc.; Esclaves -- Romans, nouvelles, etc.; African Americans; Fugitive slaves; Master and servant; Plantation life; Slavery; Enslaved persons; Southern States; Political fiction.; Fiction; Political fiction; Didactic fiction.